The Effect Of Management Information System On The Work Effectiveness Of ASN At BPKAD, Bengkulu City - Apriana Apriana; Siswanto Siswanto; Ermy Wijaya (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the effect of management information systems on the work effectiveness of ASN at BPKAD Bengkulu City. The results showed that there was an influence of management information systems on the work effectiveness of ASN BPKAD Bengkulu City, with the test results obtained t count > t table (12.837 > 2.002) with The regression equation Y = 16.84 + 0.53X means that for every 1 unit increase in the value of the management information system variable, the ASN work effectiveness variable will increase by 0.53 at the Bengkulu City BPKAD. The value of the correlation coefficient (r) of 0.63 indicates that there is a strong influence between the management information system on the work effectiveness of ASN BPKAD Bengkulu City because it is in the interval 0.60-0.799. The Coefficient of Determination (KD) value of 40.1% means that the contribution of management information systems to the work effectiveness of ASN BPKAD Bengkulu City is 40.1% and 59.9% is influenced by other variables not examined.